Kesehatan Mental Perinatal Dan Luaran Menyusui - Rahmaika Arumsari, Dita; Sukma, Febi; Istiananingsih, Yuni (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Breastfeeding and maternal mental health in the perinatal period are two important issues in public health. Breastfeeding is the most ideal way to feed babies and has positive short and long term impacts for both mothers and babies. Breastfeeding is a natural process, but many mothers experience problems and feel pressured by breastfeeding. Mothers who had high levels of anxiety and/or depression (high scores on psychometric tests that detect mental health disorders) before or during pregnancy or after delivery had more difficulties with breastfeeding than others. The aim of this study was to synthesize the results of current research on the relationship between perinatal mental health and breastfeeding outcomes. This study uses the literature review method. Literature searches used Pubmed, Tandfoline, Science Direct, and Google Scholar in 2018 – 2022. Articles were screened independently by researchers using the PRISMA method. Based on the 11 articles analyzed, it was shown that most of the longitudinal studies showed a relationship between perinatal mental health and breastfeeding outcomes. Other longitudinal studies also explain the existence of a two-way causality relationship between perinatal mental health and breastfeeding outcomes variables. Perinatal mental health influences practice and continuity of breastfeeding. Conversely, the practice and continuity of breastfeeding also affects the mental health of mothers after giving birth.